Palaeomagnetic Results From the Indian Heaven Volcanic Field, South‐Central Washington: Palaeomagnetism of Indian Heaven volcanic field - Mitchell, R. J.; Jaeger, D. J.; Diehl, J. F.; Hammond, P. E. (Geophysical Journal International, 1989)
Palaeomagnetic data have been obtained from Plio‐Pleistocene rocks of the Indian Heaven volcanic field (IHVF) located in the High Cascade province in southern Washington. Alternating field demagnetization yielded well‐defined directions from 56 individual lava flows (sites) from 23 volcanic units. All units sampled were normally magnetized suggesting that volcanic activity within the Indian Heaven region occurred primarily during the last 0.73 Myr and not over the last 3.75 Myr as suggested by K‐Ar ages. Combining palaeomagnetically similar site mean directions from lava flows from the same volcanic unit resulted in N= 35. the mean direction calculated from this data set is I= 65.2° and D = 0.2° (095 = 3.3°; k = 56.4) while the palaeomagnetic pole [calculated using virtual geomagnetic pole (VGP) data] is located at 87.7°N, 231.4°E (or95 = 4.7; k= 27.2). This pole is not significantly different from the pole determined from all data (N= 56) or the rotational axis and is slightly near‐sided with respect to the mean sampling site longitude. the between‐site angular dispersion of the VGPs about the mean for N‐35 and N= 56, although low, is not statistically different at the 95% confidence level from the expected value predicted by model F of McFadden & McElhinny (1984). Our data, together with other recent data from the western United States, do not confirm the presence of a persistent standing non‐dipole field component in this region during the Plio‐Pleistocene as suggested by Brown & Mertzman (1979). Additionally, these data suggest that VGP angular dispersion associated with the geomagnetic field has been decreasing over the last 5 Myr. Copyright © 1989, Wiley Blackwell. All rights reserved